Cyberbullying and its Relationship with Smartphone Addiction - Maharjan, Rocky; Gurung, Laxmi (Mangal Research Journal, 2022)
Smartphone and internet overuse can result into severe problems in users’ personal and social lives. In this backdrop, the present study aims to find the relationship between cyberbullying and smartphone addiction among BBA students. Participants were 123 males and 157 female students whose ages ranged from 17 to 29 years. The questionnaire with Smartphone Addiction Scale- Short Version (SAS-SV) and Revised Cyber Bullying Inventory-II (RCBI-II) were used to assess the smartphone addiction and cyberbullying respectively by using a convenience sampling method. The cyberbullying perpetration was reported by nearly 30% respondents and more than 60% respondents were victimized by cyberbullying. The password hacking and sending embarrassing and hurtful messages were common in cyberbullying. The study found that male students were significantly involved in cyberbullying perpetration. The study further revealed that time spent on smartphone in a day was significantly associated with both cyberbullying perpetration and cyberbullying victimization. This study found significantly positive correlation between smartphone addiction, cyberbullying perpetration and cyberbullying victimization. These results suggest the need to develop educational programme to educate the students to use smartphone effectively and safely to prevent cyberbullying.